Assessing the COVID-19 pandemic impact on tourism arrivals: The role of innovation to reshape the future work for sustainable development - Najid Ahmad; Shuyun Li; Mouna Hdia; Jaroslav Belas; Wan Mohd Hirwani Wan Hussain (Journal of Innovation & Knowledge (JIK), 2023)
The current COVID-19 pandemic has generated unprecedented disruption in the tourism sector, requiring innovative solutions to reshape future work for sustainability. Despite the several benefits of tourism and innovation, studies examining the interlinkages among tourism, pandemic uncertainty, and innovations for sustainability are rare. To fill this gap, this paper investigates the impact of the pandemic on tourism arrivals, and the effects of tourism arrivals and pandemic impacts on the sustainable development of France. The paper further considers the innovation influences on pandemic uncertainty to consider it key for the control of the pandemic. Autoregressive distributed lag results based on 25 years of historical data show that the immediate effects of pandemic discussion on tourism arrivals are insignificant. However, in the long run, such effects become significantly negative, revealing that a rise in pandemic discussion reduces tourism arrivals in France. We find that tourism arrivals and pandemic discussions have positive significant effects on the sustainability of France. The tourism arrivals and pandemic discussion interaction results reveal that tourists who are aware of the pandemic significantly contribute to sustainability. Significant evidence shows that a rise in innovation helps to reduce pandemic uncertainty. However, innovation's short-term effects are more prominent compared with the long-term effects, indicating that the pandemic can be countered in the short run with the help of innovative solutions. Thus, relying on innovation, especially innovations related to COVID-19 will reduce the pandemic's risk. Our results were robust to various econometric methodologies. We have drawn policy implications to focus on tourism development and constant innovations for sustainable recovery.
Keywords: 650; COVID-19 pandemic; Future work; Innovation; Sustainability; Tourism